Examining the Associations Between Online Interactions and Momentary Affect in Depressed Adolescents - Moukalled, Summer H.; Bickham, David S.; Rich, Michael (Frontiers in Human Dynamics, 2021)
Concern has been raised over parallel increases in youth depression and online interactive media use over the past two decades. The aim of this study was to determine whether online interactions are associated with users’ affective states. Using ecological momentary assessment, we measured depressed adolescents’ momentary affect during and residual feelings following online interactions with offline friends and family, online friends, and acquaintances/strangers. We found that depressed adolescents use texting services and social networking sites to interact online, most frequently with offline friends and family, followed by online friends. Results of generalized estimating equations showed associations between negative affect and digital interactions with offline friends and family. Participants were less likely to report feeling better after interacting with online friends than after interacting with any other relationship type. Our findings highlight the heterogeneity of depressed adolescents’ online interactions and suggest that their affective experience varies depending on the nature of the relationships they have with those with whom they interact.